Antidepressant Shugan Jieyu Capsule Alters Gut Microbiota and Intestinal Microbiome Function in Rats With Chronic Unpredictable Mild Stress -Induced Depression - Tan, Jingxuan; Li, Xixuan; Zhu, Ying; Sullivan, Mitchell A.; Deng, Bin; Zhai, Xuejia; Lu, Yongning (Frontiers in Pharmacology, 2022)
Shugan Jieyu Capsule (SG) has been widely used in China to treat mild to moderate depression. Hypericum perforatum L. (St John’s Wort, SJW) is the main ingredient of SG and has been used as herbal medicine to treat depression in western countries. However, it is known that SJW has low bioavailability and does not easily get through the blood-brain barrier. Therefore, how SG plays an antidepressant effect in the central nervous system (CNS) remains an urgent problem to be solved. Mounting research has described the relationship between antidepressants and intestinal microbiota to illuminate antidepressive mechanisms in the CNS. We aimed to investigate the effects of therapy with SG on the function of gut microbiota and intestinal microbiota in rats with chronic unpredictable mild stress (CUMS)-induced depression. The psychophysiological state and the hypothalamic-pituitary-adrenal axis function of rats are evaluated through behavioral experiments, corticosterone levels, serotonin levels, and adrenal index measurements. 16S rDNA amplicon sequencing is used to test the changes in gut microbiota and make functional predictions of genes. With treatment of SG, the depression-like behaviors of CUMS-induced rats were reversed; the corticosterone levels and the adrenal index decreased significantly; the level of serotonin increased significantly; and the alpha and beta diversity analysis of microbiota showed an increase in the richness and uniformity of the flora were increased. SG regulated the relative abundance of Actinobacteria, Erysipelotrichaceae, Bifidobacteriaceae, Atopobiaceae, Dubosiella, and Bifidobacterium; Linear discriminant analysis effect size analysis demonstrated that Lactobacillaceae (family level), Lactobacillus (genus level), Lactobacillales (order level), Bacilli (class level), and Lactobacillus-reuteri (species level) were biomarkers in the SG group samples, and also likely to modulate metabolic pathways, such as those involved in carbohydrate metabolism, amino acid metabolism, and signal transduction. These data clearly illustrated the effect of SG on gut microbiome, thus laying the foundation for uncovering more insights on the therapeutic function of the traditional Chinese antidepressants. The potential of SG on mechanisms of antidepression to alter gut microbiota and intestinal microbiome function exposed to CUMS can be explored.